Coffee & Community: Heritage to Innovation - Maspul, Kurniawan Arif (Indonesian Journal Publisher, 2025)
Specialty coffee entrepreneurship in Saudi Arabia has emerged as a dynamic catalyst for economic diversification, cultural preservation, and sustainable development under Vision 2030. This study examines how youth-led ventures, supported by a 320 million Public Investment Fund initiative, are revitalizing traditional gahwa rituals while driving a 1.54 billion market projected to grow at 5.1% annually (Maspul, 2025; Arab News, 2023). Through qualitative analysis of stakeholder interviews, ethnographic case studies, and policy documents, the research reveals a sector where 72% of young Saudis engage weekly with coffeehouses, 37% of the workforce is female, and CRISPR-engineered drought-resistant crops combat climate threats in Jazan. Digital platforms like COFE App bridge heritage and modernity, while UNESCO-recognized Khawlani coffee fosters global soft power. The findings underscore coffee’s role in advancing gender equity, circular economies (e.g., 30% waste reduction via biodegradable packaging), and halal-certified exports targeting a 3.2 trillion market. Policy recommendations prioritize youth training academies, climate-smart agriculture, and strategic global partnerships. This study positions Saudi Arabia’s coffee renaissance as a blueprint for reconciling tradition with innovation, offering lessons in community resilience and sustainable growth for economies worldwide.